EGF Stimulates Rab35 Activation and Gastric Cancer Cell Migration by Regulating DENND1A-Grb2 Complex Formation - Ye, Bixing; Duan, Biao; Deng, Wenjie; Wang, Yueyuan; Chen, Yan; Cui, Jie; Sun, Shixiu; Zhang, Yujie; Du, Jun; Gu, Luo; Lin, Lin; Tang, Yurong (Frontiers in Pharmacology, 2018)
Aims: The aim of this study was to reveal the specific molecular mechanisms by which DENND1A accepts EGF signaling and activates Rab35 in gastric cancer. Methods: The expression of proteins related to DENND1A was examined by western blot analysis. Activation of Rab35 was assessed by GST-pulldown. The interaction of DENND1A and Grb2 was assessed by GST-pulldown and coimmunoprecipitation assays. The relationship between DENND1A and cell migration and invasion was detected using wound healing and transwell by gene overexpression and RNA interference. Results: EGF stimulation significantly promoted cell migration, whereas transfection with siRab35 partially inhibited EGF-promoted cell migration. DENND1A is also involved in these processes and active Rab35. Moreover, DENND1A binds to the N-terminal and C-terminal SH3 domains of Grb2 through PRD. Of special interest is the observation that EGFR can recruit Grb2-DENND1A complex under EGF stimulation. Further results reveal that the higher the expression of DENND1A, the shorter progression-free survival of gastric cancer patients. Conclusions: In summary, we confirmed that EGF-Grb2-DENND1A-Rab35 signaling pathway with the interaction of DENND1A and Grb2 as a regulatory center could regulate gastric cancer cell migration and invasion. Ultimately, the expression level of DENND1A predicts the survival status of gastric cancer patients and may become one of the important targets for the treatment of gastric cancer.